PEMANFAATAN CHATGPT PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNTAN - Charminita, Dwi Sarah; Maria Ulfah; Muhammad Basri (Universitas Tanjungpura, 2026)
The development of artificial intelligence technology, particularly ChatGPT, has brought changes to learning practices in higher education. Students are increasingly utilizing ChatGPT as an aid in completing academic tasks and supporting independent learning processes. This study aims to analyze the Utilization of ChatGPT among Students of the Economic Education Study Program at FKIP Universitas Tanjungpura, both in assisting the completion of academic assignments and as scaffolding for learning to generate creative ideas and support students' independent thinking processes. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving 11 informants, including three lecturers and eight active students who used ChatGPT in their academic activities. The results indicate that the utilization of ChatGPT is influenced by students’ perceptions of ease of use and perceived usefulness. ChatGPT helps students understand tasks, accelerates the completion of academic work, and facilitates the search for references and idea development. In addition, ChatGPT serves as a scaffolding for learning that supports critical thinking and creativity among students when used actively, reflectively, and accompanied by information verification. However, passive and excessive use of ChatGPT has the potential to create dependency and reduce the intensity of independent thinking and creativity among students. Therefore, it can be concluded that ChatGPT has the potential to be an effective learning aid if used wisely. The role of lecturers and students’ academic awareness are crucial in ensuring that the use of ChatGPT remains aligned with learning objectives and academic ethics.